Archery and Swimming in Relation to Security Education as Curriculum Design in Tackling Security Challenges among Nigerian Schools - Danzaria, Nasir; Okam, Clement Chukwueloka; Magaji, Umar Sale (International Research-Based Education Journal, 2025)
This study explores the integration of archery and swimming into Security Education as a curricular design aimed at addressing security challenges in Nigerian schools. The paper is divided into two parts: the first part elucidates the themes present in the primary and junior secondary school Security Education curriculum, as well as the concepts of archery, swimming, curriculum, curriculum design, and security. The second part discusses archery and swimming as components of curricular design, various archery shooting styles, basic swimming strokes, the functions of swimming, and how archery and swimming curricula have been implemented in other countries. The findings suggest a pressing need to include archery and swimming within the Security Education curriculum of the 9-Year Basic Education and Senior Secondary Schools in Nigeria. Additionally, the involvement of traditional archers and swimmers, along with private swimming pool owners, in teaching these skills to students is highly recommended.